Development of galts and role of M cells towards feed-based vaccine against Streptococcus iniae infection in red hybrid tilapia (Oreochromis sp.) - Hayat, Mohammad (2019)
This study was conducted to determine the IgM antibodies, development of gutassociated lymphoid tissues (GALTs) and M cell’s role due to streptococcosis in red hybrid tilapia following oral administration of feed based formalin killed vaccine (FKV) of S. iniae and challenged with live S. iniae. Three hundred red hybrid tilapia fish of 80 ± 10 g were divided into 6 major groups (1A, 1B, 2A, 2B, 3A, 3B). Each group consisted of 50 Red hybrid tilapia fish, kept in duplicate 2000 L glass aquaria. At week 1, all fish from the groups 1A,1B, 2A, 2B were started to feed with the feedbased FKV of S. iniae for different weeks and boosters dose were administered to group 2B only on day 14 and 21. Groups 3A, 3B were kept as negative (unchallenged) and positive (challenged) control groups respectively without vaccination and fed with normal commercial pellet (Cargill) throughout the experiment. At week 4, all the remaining tilapia from each groups except 3A were challenged intraperitoneally (i.p.) by injecting 0.5mL of the inoculums containing 1 × 106 CFU/mL of live S. iniae. Fish from each groups (except 3A) were sacrificed on a weekly basis for the entire 6 weeks for the collection of serum, body surface mucus and gut lavage fluid for the evaluation of antibody responses by indirect ELISA. Upon i.p. challenge, clinical signs were observed in the vaccinated groups 1A,1B, 2A, 2B and positive control group 3B. The clinical signs included exophthalmia, body discoloration, lethargy, erratic swimming, and haemorrhagic eye. The groups 2A, 2B had the lowest mortality rate ranging from 45-30% compared to groups 1A, 1B with 80-55% and group 3B 100% respectively. Necropsy findings included nephritis, splenomegaly and haemorrhagic brain. In all vaccinated groups Red hybrid tilapia hindgut showed the presence of GALTs. The diameter of GALTs in groups 1A,1B were significantly lower (p > 0.05) compared to groups 2A, 2B whereas there was no observation of GALTs in group 3B. Results for humoral response, the groups 1A,1B, 2A and 2B had significant (p < 0.05) increasing levels of antibody as early as week 1, but absent in groups 3B. The serum IgM levels of groups 1A,1B showed similar pattern as those of groups 2A, 2B but remained lower than the groups 2B. Group 2B was significantly higher (p < 0.05). Meanwhile, group 3B did not show any significant (p > 0.05) changes throughout the experiment and all fish died at week 5 after challenge. Similar findings were recorded for the mucus and gut lavage IgM antibody levels between the treatment and 3B group. For the IHC staining, group 3B recorded the highest antigen intensity, followed by groups 1A,1B with moderate intensity and lowest in groups 2A, 2B at 12 h, 24 h, 24 h, 48h and 72 h respectively. SEM results revealed in groups 1A,1B, intestinal M cells were relatively depressed and had an irregular apical surface, with darker, short, and uneven microvilli. In groups 2A, 2B, M cells increased in size, number and vertically projected as a result of frequent and booster feeding of FKV. There were inflammatory indications in the group 3B. Nevertheless, group 3A showed slightly upward projection of intestinal M cells with normal dome epithelium. In conclusion, the FKV had a better protection rate by stimulating the production of GALTs within the lamina propria of Red hybrid tilapia hindgut, as well eliciting humoral response following oral vaccination. The IHC and SEM findings showed the existence of antigens and M cells in the villous epithelium. GALTs and villous M cells in red hybrid tilapia are important biological component of the mucosal immunity and promotes the resistance to streptococcal pathogens.